The Interactive Work of Implementing Synchronous Video‐Conference Calls—A Qualitative Study Within Early Intervention for Infants With Childhood‐Onset Neurodisability - Phillip Harniess; Anna Purna Basu; Deanna Gibbs; Jeff Bezemer (Health Expectations)
ABSTRACT Introduction This study explores the ‘peripandemic’ implementation of synchronous videoconference calls during COVID‐19 for delivering physiotherapy early intervention services to families of infants with childhood‐onset disability. The interactional experience of conducting early intervention through videoconference calls is under researched. We aimed to understand parents' and therapists' experiences of communication and learning within early intervention sessions for infants with cerebral palsy conducted via video conference calls. Methods Data were collected through interviews, video case studies and focus groups involving 15 parents and 16 therapists. We used qualitative analytical methods inspired by grounded theory and multimodality. Results Undertaking early intervention sessions via synchronous videoconference calls creates complexities and disrupts communication norms between parent, therapist and infant. These audio‐visual constraints have implications for developing shared understanding and learning. Resolving these challenges necessitated increased interactive work within the parent–therapist partnership. The onus placed on parents to have additional logistical roles in some circumstances created strain, which diverted attention from optimal learning. Conclusion The post‐pandemic healthcare landscape pushes for digital innovation challenging traditional therapy models. Our contribution outlines that while videoconference calls may improve efficiency, they also add cognitive load and interaction challenges, which require modification to routine in‐person session designs. We provide recommendations for adaptive implementation strategies for videoconference calls that will benefit from further iterative codesign cycles. Public and Patient Contribution We partnered with parents through public and patient involvement. Parents (n = 9) who were previous NHS early intervention service users formed the Parent Advisory Group (PAG). These parent partners came from a variety of backgrounds and provided their unique perspectives to directly contribute and guide decision‐making throughout the project. Their contribution influenced approach to recruitment and consent; the participant information and consent form development; topic guide development; considerations of the use of video in the project design and sense checking of analytical interpretations.